Aplikasi HC-Furniture Untuk Penjualan Produk Mebel - Green Ferry Mandias; Oktoverano Lengkong; Feldryansa Somba; Maria Andriani Sambur (Fakultas Ilmu Komputer, Universitas Klabat, 2022)
The improvement of technology today is highly expected because it has an impact on human needs every day. There are still many people who have not taken advantage of these technological developments in this case as a medium of buying and selling, especially furniture. The current sales system still uses manual or offline methods so that prospective customers still have to go to store or place of business and it takes quite a long time. By utilizing existing technological facilities, sellers and buyers can trying to make better sales facilities. So the business of selling furniture needs technology as a medium to make it easier for seller and buyers to make transactions. Therefore, the researchers will developed an android-based mobile application, namely HC-Furniture which aims to make it easier for customers to get information about various products and help increase the sales power of furniture business owners. The research uses Agile software development method, the framework used is react-native, and firebase as a realtime database to store data. Based on the results of the study, we can see the application developed can running and can help connect sellers and buyers of furniture products and make easier to market furniture products.